Blockholder Ownership Impact on the Related Party Transactions to the Financial Industries - Supatmi Supatmi; Ines Aprilia Primadani (Universitas Pendidikan Ganesha, 2021)
Research on the impact of ownership structure on related party transactions carried out by companies gives varied results. Moreover, this research still rarely uses a sample of the financial industry in Indonesia. So, the study aimed to find out block holder ownership effect on tunnelling or propping related party transactions in financial industries in Indonesia. Sample research were 82 financial industries that listed in Indonesian Stock Exchange in 2017-2019 with 246 observations as panel data. Based on panel data regression test, this study found block holder ownership had positive effects on tunnelling related party transactions that proxied by related party transactions related to accounts receivable and related party transactions related to assets other than account receivables. Meanwhile, blockholder ownership had no effect on propping related party transactions that proxied by related party transactions related to accounts payable and liabilities other than accounts payable. The study also found blockholder ownership effect on tunnelling related party transactions was bigger than propping. These findings were appropriate with the relevant agency theory about blockholder ownership effect on related party transactions which had the potency on the emergence of agency conflict among the shareholders.